Analysis of explosion in concrete by axisymmetric FE-SPH adaptive coupling method. Issue 4 (27th May 2014) - De'an, Hu; Chunhan, Liu; YiHua, Xiao; Xu, Han
Abstract : Purpose: – The purpose of this paper is to confirm that the axisymmetric finite element and smoothed particle hydrodynamics (FE-SPH) adaptive coupling method is effective to solve explosion problem in concrete based on the experiments. Design/methodology/approach: – Axisymmetric FE-SPH adaptive coupling method is first presented to simulate dynamic deformation process of concrete under internal blast loading. Using calculation codes of FE-SPH coupling method, numerical model of explosion is approximated initially by finite element method (FEM), and distorted finite elements are automatically converted into meshless particles to simulate damage, splash of concrete by SPH method, when equivalent plastic strain of elements reaches a specified value. Findings: – In this paper, damage process and pressure curve of concrete around explosive are analyzed and buried depth of explosive in concrete influence on damage effect under internal blast loading are obtained. Numerical analyses show that FE-SPH coupling method integrates high computational efficiency of FEM and advantages of SPH method, such as natural simulation to damage, splash and other characteristics of explosion in concrete. Originality/value: – This work shows that FE-SPH coupling method has good performance to solve the explosion problem.